CLINICAL AND INSTRUMENTAL FEATURES OF DIAGNOSTICS OF COMBAT SURGICAL CHEST INJURY WITH TISSUE DEFECTS - Korol, S.O.; Aslanian, S.A.; Chelishvili, A.L.; Vovk, M.S.; Honcharuk, V.S.; Palii, I.P.; Melnychenko, O.O. (World of Medicine and Biology, 2023)
Retrospective analysis of the results of comprehensive diagnostic examination of 127 injured persons with combat surgical chest injuries and their complications (bronchopleural fistula and pleural empyema) was conducted. Injured military servicemen with thoracic wall tissue defects in combat thoracic trauma at the III and IV levels of medical care were analyzed. Two clinical groups were defined: the main group and the comparator group. Clinical, laboratory, microbiological and instrumental research methods were used to examine injured servicemen and monitor clinical course of traumatic disease. To identify anatomical and morphological features of chest injuries, instrumental methods were used, with preference given to X-ray and ultrasound methods. During diagnostic examination of lungs and pleural cavities using computed tomography, compared to chest X-ray examination, 8.6 % more cases of pneumothorax/pneumohydrothorax, 14.1 % more cases of hydrothorax, 22.8 % more cases of pneumonia were identified, as well as new syndrome categories were identified: subpleural hematoma, pleural thickening.
Keywords: combat thoracic trauma; thoracic wall defects